Limonene against GABAA and 5-HT2A receptors: psychopharmacological potential evaluated by docking and ADMET - Jackson Oliveira Sousa, Adam; de Araújo Feitosa, Nataly; Celina Feitosa de Araujo, Maria; Alves da Silva, Daniel; Lacerda Loiola, Daniel; Cavalcante Nunes, Railo; Fernandes Lima, Jakson; Silva Sobreira, Rairam; Emanuele Braga Souza de Assis, Carine; Junior Beserra Sobreira, Carlos; Eranildo Teles do Nascimento , José; Fernandes Lima, Glória; et al. (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Natural products, especially metabolites from essential oils, have been receiving increasing attention in pharmacology due to their therapeutic potential and lower risk of adverse effects. Limonene, a monoterpene found in species of the Rutaceae family, has been associated with anxiolytic and antidepressant effects. This study evaluated, through molecular docking analyses, the interactions of limonene with GABAA receptor subunits (α1, α2, α3, α5) and with the 5-HT2A receptor. SwissADME, pkCSM, ADMETlab 3.0, and ProTox 3.0 were employed for pharmacokinetic and toxicogenomic predictions, while HEX 8.0.0 was used for molecular docking, with diazepam (DZP) and fluoxetine (FLU) as reference controls. The interactions were further inspected using PyMOL 1.4.7 and Discovery Studio 2021. The results indicated a favorable pharmacokinetic profile, good bioavailability, absence of significant toxicity, and binding affinity comparable to the reference drugs. Interactions with functional receptor residues suggest potential anxiolytic and antidepressant modulatory effects. Overall, the findings highlight limonene as a promising candidate for the development of novel phytopharmaceuticals, warranting further in vitro and in vivo validation.